A mixed-methods study of the awareness and functionality of sexual and reproductive health services among persons with disability in Ghana - Abdul-Aziz Seidu; Bunmi S. Malau-Aduli; Kristin McBain-Rigg; Aduli E. O. Malau-Aduli; Theophilus I. Emeto (Reproductive Health, 2023)
Abstract Background Persons with disabilities (PwDs) face barriers in accessing sexual and reproductive health (SRH) services due to lack of knowledge and awareness, stigma and discrimination, and inadequate service provision. This study aimed to examine the determinants of SRH knowledge and awareness among PwDs in Ghana, and to explore their perceptions of the functionality of SRH services. Methods A sequential explanatory mixed-methods study design was used to collect and analyse quantitative (n = 402) and qualitative (n = 37) data from PwDs in two districts in Ghana. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data was analysed thematically. Results Most of the participants had high awareness of SRH (94.3%), sexually transmitted infections (STIs) (92.5%) and HIV/AIDS (97.0%). Employment status was positively associated with SRH awareness [aOR = 1.62; 95% CI = 1.02, 2.59]. Disability type was a significant predictor of STI [aOR = 2.02; 95% CI = 1.39, 2.94] and HIV/AIDS [aOR = 2.32; 95% CI = 1.21, 4.44] awareness, with the visually impaired having higher odds than the physically disabled. Age group was also a significant predictor of STI awareness, with older respondents having higher odds than younger ones [aOR = 1.76; CI = 1.01,3.05 for 30–39 years; aOR = 2.48; CI = 1.22, 5.05 for 40–49 years]. The qualitative findings revealed four main themes: conceptualisation of SRH, active engagement in SRH information seeking, tensions between knowledge and religious beliefs and perceived utility of SRH services. Conclusion Despite the high levels of SRH knowledge and awareness among PwDs, there are significant gaps and challenges related to disability type, age group, misconceptions, beliefs, and service non-functionality that limit the utility of SRH services. The findings call for tailored education to reduce misconceptions and put in pragmatic steps to deliver quality SRH services and information to PwDs. Further research is needed to assess the sexual lives of PwDs and explore the perspectives of all relevant stakeholders, including service providers and policymakers on how to enhance SRH outcomes for PwDs in Ghana.